Giant left main coronary artery to right atrium fistula. Issue 1 (3rd December 2010) - Gualis, Javier; Castaño, Mario; Gómez-Plana, Jesús; Mencía, Pilar; Martín, Carlos; Martínez, Jose M; Alonso, David; De Miguel, Antonio; De Diego, Alejandro
Abstract : Aneurysmal arterial origin of coronary fistulae is an extremely rare combination. We report a case of a giant left main coronary artery to right atrium fistula in a 48-year-old male. We describe the clinical course and management options.